THE INFLUENCE OF CONSUMER TRUST AND PERCEIVED VALUE ON CONSUMER PURCHASE DECISION OF E-COMMERCE IN SOCIAL MEDIA (STUDY CASE IN MANADO) - Liusito, Reginald A.; Tulung, Joy E.; Saerang, Regina T. (Universitas Sam Ratulangi, 2020)
Abstract: In this digital era, technological advances cannot be dammed especially in the field of business with an online platform making business activities become tighter due to massive competition. Thus, making purchase decisions absolutely controlled by consumers. The power of consumers in determining the purchase of a product makes producers competing to seduce consumerâ€™s buying interest. The ability of producers to meet the needs and wants of consumers is the key to success in business activities.Â This research aims to find out the influence of consumer trust and perceived value on consumer purchase decision of e-commerce in social media. Consumer trust variable consists of perceived integrity, perceived competence, perceived security control, and benevolence. Perceived value variable consists of emotional value, social value, quality/performance, and value price/value of money. This study uses purposive sampling that only observes people who have shopped online through social media. The sample is 100 respondents and analyzed using Multiple Linear Regression analysis. The results of this study have shown that perceived integrity, perceived competence, perceived security control, and benevolence contribute positively to consumer trust. Emotional value, social value, quality/performance, and price/value have positive contribution to perceived value. These results indicate that consumer trust and perceived value have significant and positive effect on consumer purchase decision of e-commerce in social media partially and simultaneously. This study suggests that producers should use social media as the means for selling and maximize its features so that the overall benefits can be felt.Â Keywords: consumer trust, perceived value, consumer purchase decision